2012
DOI: 10.1080/13548506.2011.608804
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of children's medically unexplained symptoms: Managing ambiguity, authenticity and responsibility

Abstract: Medically unexplained symptoms such as headache, tiredness and stomach problems are common amongst children and research highlights the potential importance of the family environment in their development and maintenance. The present qualitative study aimed to explore how mothers make sense and manage their child's unexplained recurrent somatic symptoms. Mothers (n=13) with children with headaches, tiredness or stomach problems were interviewed. Transcripts were analysed using thematic analysis. Three main area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…, Webb et al . , Morris & Ogden ). A qualitative study of 21 UK young people with a diagnosis of CFS/ME suggested that they wanted HCPs to listen to their experiences, although this did not always happen in practice (Richards et al .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…, Webb et al . , Morris & Ogden ). A qualitative study of 21 UK young people with a diagnosis of CFS/ME suggested that they wanted HCPs to listen to their experiences, although this did not always happen in practice (Richards et al .…”
Section: Resultsmentioning
confidence: 97%
“…, Hareide et al . , Morris & Ogden ). In one small UK qualitative study of 13 mothers of children with recurrent unexplained symptoms, mothers reported feeling that symptoms were authentic and real, and required medical intervention (Morris & Ogden ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations